A bibliometric analysis of undergraduate thesis submitted to the University of the Philippines Manila-College of Pharmacy Library from 2008-2018 - Bautista, Darren Lambert V.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
This study used a bibliometric analysis as a collection oriented measure to analyze the citations used in the thesis submitted to the University of the Philippines Manila – College of Pharmacy Library from A. Y. 2008-2018 with a total of 4,819 citations recorded from 183 undergraduate theses of the two program Bachelor of Science in Pharmacy and Bachelor of Science in Industrial Pharmacy.

Results showed that the core subject distribution is skewed to BS Pharmacy with over half of the collected thesis titles in the field as opposed to industrial Pharmacy and Pharmaceutical Chemistry. The results showed that the work of M. M. Loquias and Y. R. Robles titled “Issues and concerns on 55 utilization of the pharmacy workforce in the Philippines” in 2012 is still the most relevant work used as reference while M. Hojat is the most cited author.

This study used three metrics of centralization to further dive into the quantitative analysis perspective. The result named J. Lee as the topped degree centrality measure with a score of making him the influential author in the network. The results determined that there is a little deviation within the closeness centrality which means that all authors in the network have almost the same opportunity to collaborate with one another while betweenness centrality measured H. Lee to be the most likely to control access within the network with score of 1514.3

The methodology used in the study offers a new approach to library collection evaluation. These measures effectively showed the relevance of titles and authors in the field such as proving the relevance of local works within the student’s choice of reference and the relevance of dated publication to modern take on Pharmacology. The study also showed levels of centralization within the collaborative network that assessed the ease of access, level of support and authority among authors and the dependence of each work to another.
Thesis (Bachelor of Library and Information Science)
Keywords: Bibliometric analysis; University of the Philippines (Manila) College of Pharmacy Library -- Bibliometric analysis